Programmed cell death of the nucellus during Sechium edule Sw. seed development is associated with activation of caspase-like proteases - Lombardi, Lara (Journal of experimental botany, 2007)
The nucellus is a maternal tissue that embeds and feeds the developing embryo and secondary endosperm. During seed development, the cells of the nucellus suffer a degenerative process soon after fertilization as the cellular endosperm expands and accumulates reserves. Nucellar cell degeneration has been considered to be a form of developmentally programmed cell death (PCD). It was investigated whether or not this degenerative process is characterized by apoptotic hallmarks. Evidence showed that cell death is mostly localized in the border region of the tissue adjacent to the expanding endosperm. Cell death is accompanied by profound changes in the morphology of the nuclei and by a huge degradation of nuclear DNA. Moreover, an increase of activity of different classes of proteinases is reported, and the induction of caspase-like proteases sensitive to specific inhibitors was detected. Nucellar caspase-like proteases are characterized by an acid pH optimum suggesting a possible localization in the vacuole